INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA ARAB DI SEKOLAH MUHAMMADIYAH - Syahnaidi, Muhammad Amin Qodri; Baroroh, R. Umi (Arabi : Journal of Arabic Studies, 2018)
This study aimed to determine the planning of character education integration in Arabic learning, the implementation of the integration and the implications of character education on the students' character in Muhammadiyah Middle School 10 Yogyakarta. This was a qualitative research. Data were collected by observation, interviews and documentation. Data was analyzed using qualitative descriptive methods. The results showed: (1) Planning for the integration was included into syllabus and lesson plans. The integration of character education was carried out in the philosophical, material and strategic domains. (2) The implementation of character education integration in Arabic language learning was done through learning activities, giving advice, and the teacher's role model in Arabic teaching. At the stage of implementation, the integration  had been carried out in the philosophy, material and strategy domains. (3) The implications of character education on students' character were the development of religiousity, obedience, discipline, communicativeness and responsibility.